A moral atmosphere of development as a share: Consequences for urban development in Indonesia. (August 2018) - Jakimow, Tanya
Highlights: A moral logic of 'development as a share' permeates development in Indonesia. There are emotional consequences of this moral logic that go beyond its practices. Moral atmosphere reveals the way 'development as a share' permeates the arena. Moral atmospheres influence resource distribution, relations and subjectivities. Abstract: Corruption is a social preoccupation in Indonesia, receiving as much attention in the media as it does in journals such as World Development . The consequences of this preoccupation have escaped the attention of scholars however, a lacuna that this article addresses. Through ethnographic research of sites of state-led welfare and community driven development in Medan, Indonesia, I trace the emergence of a moral logic characterised by bagi-bagi, or development as a share. National anti-corruption discourses, lived experiences of petty corruption, and the failures of development projects to bring meaningful benefits encourage various stakeholders to manoeuvre to get a share, or take their part from the resources that flow from the state. The impact of this logic exceed its practices, however. I advance the concept of moral atmosphere to reveal the emotional and affective consequences, the ways the ever-present possibility of bagi-bagi permeates development encounters and marks individuals as objects of suspicion. Through the empirical material, I demonstrate the ways the moral atmosphere of bagi-bagi influences subjectivities, social relations, and the distribution of resources, and hence the importance of examining it as an element of the development arena.